2023
DOI: 10.1073/pnas.2301055120
|View full text |Cite
|
Sign up to set email alerts
|

The role of tropical rainfall in driving range dynamics for a long-distance migratory bird

Bryant C. Dossman,
Colin E. Studds,
Shannon L. LaDeau
et al.

Abstract: Predicting how the range dynamics of migratory species will respond to climate change requires a mechanistic understanding of the factors that operate across the annual cycle to control the distribution and abundance of a species. Here, we use multiple lines of evidence to reveal that environmental conditions during the nonbreeding season influence range dynamics across the life cycle of a migratory songbird, the American redstart ( Setophaga ruticilla ). Using long-term data from the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Most studies have concluded that shifts in migratory timing occur in response to changes in climate 3 . This largely precludes the possibility that shifts can be nonadaptive in nature or in response to other environmental conditions 41 . Previously, godwits were advancing their breeding ground arrival timing and appeared to be shifting in relative synchrony with the climate 11,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have concluded that shifts in migratory timing occur in response to changes in climate 3 . This largely precludes the possibility that shifts can be nonadaptive in nature or in response to other environmental conditions 41 . Previously, godwits were advancing their breeding ground arrival timing and appeared to be shifting in relative synchrony with the climate 11,21 .…”
Section: Discussionmentioning
confidence: 99%